Technology Of Black Cincau Liang Tea As Diversified Products In Black Cincau Gel Producer At Batu City - Tri Dewanti Widyaningsih (Journal of Innovation and Applied Technology, 2015)
ABSTRACT Black cincau (Mesona palustris BL) or black grass jelly is traditional beverage ingredient that is believed has efficacious for health, but the black cincau gel in the market known asunhygienic food and has shortshelf life. Liang tea of black cincau is a kind of processed product development of black cincau. Liang tea or herbal tea made from of black cincau extracts with the addition of other herbs such as ginger, cinnamon or pandan leaves. "Sumber Murni " home industry is theproducerof blackcincaugelinBatucitywhich isinterested inproducingliang tea of black cincau in a plastic cup packaging as well as product diversification for enterprise development. Therefore, Liang tea of black cincau technology package should be a well proven technology where the technology is practical, easy to introduce. Technology which applied are: 1 ) Formulation of Liang Tea is black cincau extract : water = 60 : 40 and ginger extract added = 10 % , 2 ) The process is suitable with the flow diagram, 3 ) Engineering equipment such as semi-automatic cup sealer with tank and cookers tank for blending materials with automatic stirrer .Keywords: cookers tank with automatic stirrer,liang tea of black cincau,  semi-automatic cup sealer